If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + -9y = -19 Solving X + -9y = -19 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '9y' to each side of the equation. X + -9y + 9y = -19 + 9y Combine like terms: -9y + 9y = 0 X + 0 = -19 + 9y X = -19 + 9y Simplifying X = -19 + 9y
| 6n+2-4=4 | | 3*8+7+4d-1=58 | | (x-3y)(x+3y)=36 | | Y=(7/2)^X | | -5x-4x=18 | | p/10=-4/5 | | 8x+4-17x=58 | | 17-x=39 | | 5(x-3)+4=3x-2 | | a-(-26)=88 | | 6k^2+17k+12=0 | | .06x^2+.31x+4=10 | | (X+2)+(2X-1)=4X-7 | | 4-4x-3x=-10 | | m-(-50)=-1 | | 8(2g+-5)= | | 8(2g-5)g= | | f(-x)=3x^2+2x+8 | | V=(2/3)(3.14)r^3 | | 3a^2/2x4/9a | | 4x-3(x+2y)=y+1 | | (2a^2+3y)= | | 2-10=20 | | 2(7x+3)=-3 | | 5m^2-20=2m^3-8m | | 5x^2=-220 | | 9y-8-5y+7=0 | | 15x+18y= | | (2/3)x-5=x/6 | | (6y+7)-(6+5y)=11 | | -0.10(47)+0.80x=0.05(x-4) | | (-7c*-4)+8x=12+14 |